2018
DOI: 10.1080/09540121.2018.1476665
|View full text |Cite
|
Sign up to set email alerts
|

Economic strengthening for HIV testing and linkage to care: a review of the evidence

Abstract: Delayed HIV diagnosis and enrollment in HIV care can lead to negative health outcomes for individuals and pose major barriers to achieving the UNAIDS 90-90-90 treatment targets. Household economic strengthening (HES) initiatives are increasingly used to alleviate the direct and indirect costs of HIV testing and linkage to care for those who are diagnosed. The evidence linking HES with a range of HIV outcomes is growing, and this evidence review aimed to comprehensively synthesize the research linking 15 types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Most studies examining the impact of financial incentives on HTS coverage, linkage to care, and ART retention utilize conditional incentives. These show promising short-term effects, even with small amounts of money, while long-term effects are still largely unknown [ 45 , 46 ]. The majority of this literature focuses on investigating the use of financial incentives within HTS, with many studies consistently and independently linking it with a marked increase in the uptake of services [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies examining the impact of financial incentives on HTS coverage, linkage to care, and ART retention utilize conditional incentives. These show promising short-term effects, even with small amounts of money, while long-term effects are still largely unknown [ 45 , 46 ]. The majority of this literature focuses on investigating the use of financial incentives within HTS, with many studies consistently and independently linking it with a marked increase in the uptake of services [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A scarcity of research exists that investigates the impact of financial incentives on linkage to care and retention outcomes [46][47][48][49]. Within this research, a major challenge is posed by the limited comparability of studies [46]. This is primarily due to differences in study population and setting-spanning the urban United States [50], drug injection users in India [51], and cohorts in Sub-Saharan Africa [48,[53][54][55][56].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Zimbabwe Qualitative interviews and focus groups 17 interviews and 2 focus groups with coaches and 29 interviews with circumcised (n = 13) and uncircumcised boys (n = 16) ages [14][15][16][17][18][19] There were mixed reactions to the incentives. Some participants felt that incentives increased their motivation to go for VMMC.…”
Section: Tanzaniamentioning
confidence: 99%
“…These reviews generally found that such interventions may help to increase VMMC uptake, particularly when they address specific barriers, but evidence was limited. Economic compensation, or financial incentives, have been explored for a range of HIV-related behaviors, including sexual or drug use behaviors related to HIV prevention [12,13], HIV testing [12,14], linkage to or engagement in HIV treatment [10,12,14,15], and adherence to antiretroviral therapy [12,15,16]. These interventions occur within a broader social and health system context, where there may be economic incentives for other health-related behaviors (for example, prenatal care, infant vaccinations, or insecticide-treated bednets) [17].…”
Section: Introductionmentioning
confidence: 99%